2009
DOI: 10.2215/cjn.04380808
|View full text |Cite
|
Sign up to set email alerts
|

Epoetin Therapy and Hemoglobin Level Variability in Nondialysis Patients with Chronic Kidney Disease

Abstract: Background and objectives: Intrapatient variability of hemoglobin (Hb) is a newly proposed determinant of adverse outcome in chronic kidney disease (CKD). We evaluated whether intensity of epoetin therapy affects Hb variability and renal survival in nondialysis CKD.Design, setting, participants, & measurements: We calculated the individual therapeutic index (TI) for epoetin (EPO; difference between rates of visits that required EPO dosage change and those with effective EPO change) from 1198 visits during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…Change in prevalence of Hb target during the study was analyzed by either McNemar or Cochrane's Q test. Hb stability was assessed by three methods: time-in-target [33,34] , individual SD of Hb [37] and residual SD, including slope and intercept [37] . The calculations were performed throughout the study and compared with those obtained using data retrospectively collected during the previous period in which patients were treated with darbepoetin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Change in prevalence of Hb target during the study was analyzed by either McNemar or Cochrane's Q test. Hb stability was assessed by three methods: time-in-target [33,34] , individual SD of Hb [37] and residual SD, including slope and intercept [37] . The calculations were performed throughout the study and compared with those obtained using data retrospectively collected during the previous period in which patients were treated with darbepoetin.…”
Section: Discussionmentioning
confidence: 99%
“…The cutoff dose of darbepoetin was chosen on the basis of data from randomized trials [29,32] and observational studies [33][34][35] showing that the majority of non-dialysis patients are treated with darbepoetin dose below 40 g/week.…”
Section: Introductionmentioning
confidence: 99%
“…Although some studies reported an association of Hb variability with increased mortality (23)(24)(25)(26), a more recent analysis by Brunelli et al (27), studying a more contemporaneous cohort of hemodialysis patients failed to demonstrate such an association. In the study by Brunelli et al (27), 6644 incident patients between 2004 and 2005 were evaluated.…”
Section: T He Trial To Reduce Cardiovascular Endpoints Withmentioning
confidence: 95%
“…the provider's failure to modify the ESA dose despite recognition that treatment goals are unmet, therefore, emerges as a potential determinant of Hb cycling in ND-CKD. This hypothesis was supported in our most recent study, showing that a change of ESA dose occurred in only half of control visits where it was expected on the basis of guidelines' recommendations, and that higher degrees of therapeutic inertia were associated with greater Hb variability, characterized by downward fluctuations in most cases as well as the risk of renal death [9] . This study also confirmed the role of the first ESA dose.…”
Section: Therapeutic Perspectivesmentioning
confidence: 53%
“…These findings, which resemble the discrepancy between ESA treatment and Hb outcome previously observed in HD [13,14] , suggest inadequate ESA therapy and high degrees of interpatient Hb variability in ND-CKD. To specifically address intrapatient Hb variability, we recently reviewed the clinical data obtained from 1,198 visits during the first year of ESA treatment in 137 ND-CKD patients [9] . Varying Hb was found in 85.3% with downward changes in most cases ( table 1 ).…”
Section: Hb Stability In Ckdmentioning
confidence: 99%